DEVELOPING GUIDED DISCOVERY LEARNING MATERIALS USING MATHEMATICS MOBILE LEARNING APPLICATION AS AN ALTERNATIVE MEDIA FOR THE STUDENTS CALCULUS II - Sunismi . (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstract: The development research aims to develop guided-discovery learning materials of Calculus II by implementing Mathematics Mobile Learning (MML). The products to develop are MML media of Calculus II using guided discovery model for students and a guide book for lecturers. The study employed used 4-D development model consisting of define, design, develop, and disseminate. The draft of the learning materials was validated by experts and tried-out to a group of students. The data were analyzed qualitatively and quantitatively by using a descriptive technique and t-test. The findings of the research were appropriate to be used ad teaching media for the students. The students responded positively that the MML media of Calculus II using the guided-discovery model was interestingly structured, easily operated through handphones (all JAVA, android, and blackberry-based handphones) to be used as their learning guide anytime. The result of the field testing showed that the guided-discovery learning materials of Calculus II using the Mathematics Mobile Learning (MML) application was effective to adopt in learning Calculus II. Keywords: learning materials, guided-discovery, mathematics mobile learning (MML), calculus II PENGEMBANGAN BAHAN AJAR MODEL GUIDED DISCOVERY DENGAN APLIKASI MATHEMATICS MOBILE LEARNING SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN MAHASISWA MATAKULIAH KALKULUS II Abstrak: Penelitian pengembangan ini bertujuan untuk mengembangkan bahan ajar matakuliah Kalkulus II model guided discovery dengan aplikasi Mathematics Mobile Learning (MML). Produk yang dikembangkan berupa media MML Kalkulus II dengan model guided discovery untuk mahasiswa dan buku panduan dosen. Model pengembangan menggunakan 4-D yang meliputi tahap define, design, develop, dan dissemination. Draf bahan ajar divalidasi oleh pakar dan diujicobakan kepada sejumlah mahasiswa. Data dianalisis secara kualitatif dan kuantitatif dengan teknik deskriptif dan uji t. Temuan penelitian bahan ajar ini sangat tepat digunakan sebagai media pembelajaran bagi mahasiswa. Mahasiswa memberikan tanggapan positif bahwa media MML Kalkulus II dengan model guided discovery disusun menarik, dapat dioperasikan dengan mudah melalui HP (semua HP berbasis JAVA, android, dan blackberry) sehingga dapat digunakan panduan belajar mahasiswa kapan saja. Hasil uji lapangan diperoleh bahwa bahan ajar matakuliah Kalkulus II model guided discovery dengan aplikasi Mathematics Mobile Learning (MML) efektif digunakan dalam pembelajaran matakuliah Kalkulus II. Kata Kunci: bahan ajar, guided discovery, Mathematics Mobile Learning (MML), Kalkulus II